Humorous Discourse. - Chlopicki, Wladyslaw (Humor Research HR., 2017)
This book attempts to discuss selected but thorny issues of humor research that form the major stumbling blocks as well as challenges in humor studies at large and thus merit insightful discussion. Any discourse is action, so the text-creation process is.